Early Surgical Repair of Medial Meniscus Posterior Root Tear Minimizes the Progression of Meniscal Extrusion: 2-Year Follow-up of Clinical and Radiographic Parameters After Arthroscopic Transtibial Pull-out Repair. Issue 11 (September 2020) - Moon, Hyun-Soo; Choi, Chong-Hyuk; Jung, Min; Lee, Dae-Young; Hong, Seung-Pyo; Kim, Sung-Hwan
Background: Conflicting results have been reported concerning the progression of medial meniscal extrusion (MME) after arthroscopic transtibial pull-out repair of medial meniscus posterior root tear (MMRT), and no study has evaluated the relevant factors affecting the progression of MME. Purpose: To (1) evaluate the subjective and objective surgical outcomes of arthroscopic transtibial pull-out repair of MMRT and (2) identify relevant factors affecting the progression of MME after surgery. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 63 patients who underwent isolated arthroscopic transtibial pull-out repair of MMRT between January 2010 and June 2017 were evaluated retrospectively. Clinical scores and various radiographic parameters were evaluated to assess the surgical outcomes. The patients were classified into 2 groups according to the change in medial meniscal extrusion ratio (MMER) at 1 year after surgery compared with before surgery (group 1 consisted of 21 patients with reduced or maintained MMER; group 2 consisted of 42 patients with increased MMER). Variables including baseline demographics, radiographic parameters, and arthroscopic findings were compared to identify relevant factors affecting the progression of MME after surgery. Results: In the overall cohort, clinical outcomes at postoperative 2 years improved significantly ( P < .001 for visual analog scale score, International Knee Documentation Committee subjective score, and Lysholm score), whereas radiographic parameters showed an overall deterioration compared with the preoperative level. In subgroup comparisons, a significant difference was seen in the time from the onset of symptoms until surgery ( P < .001), defined as preoperative symptom duration, which a subsequent logistic regression analysis revealed to be a relevant factor associated with the progression of MMER ( P = .015). Both groups showed progression of radiographic osteoarthritis, but the progression was significantly higher in group 2 compared with group 1 at postoperative 2 years ( P = .032). On receiver operating characteristic curve analysis, the cutoff point for preoperative symptom duration associated with the progression of MMER was 13 weeks (sensitivity, 52.4%; specificity, 76.2%; accuracy, 72.4%). Conclusion: The arthroscopic transtibial pull-out repair of MMRT showed clinical improvement but did not prevent the progression of knee osteoarthritis, MME, or MMER. Although the preservation of MMER was not capable of completely preventing the progression of knee degeneration, MMER still has a potential clinical value in delaying the rate of progression of knee degeneration. Early surgical repair of MMRT, within 13 weeks from the onset of symptoms, might be helpful to prevent the progression of MME.